POLITICAL ECONOMY OF REMITTANCES OF INDONESIAN MIGRANT DOMESTIC WORKERS IN HONG KONG DURING THE COVID-19 PANDEMIC - Florentina Dwiastuti Setyaningsih; Irwansyah Irwansyah (JWP (Jurnal Wacana Politik), 2022)
The Covid-19 pandemic has changed all aspects of people’s lives around the world, including remittances. Interestingly, Bank Indonesia in 2020 stated that remittances, the majority of which came from migrant domestic workers, from Hong Kong tended to be stable. This study uses a political economy approach to see how several economic and political factors affect the stability of the remittances of Indonesian migrant domestic workers in Hong Kong. This study uses the theory from Dilip Ratha (2003) regarding the stability of remittances during the economic crisis, where there are two factors, namely (1) the presence of automatic stabilizers in migrant worker receiving countries and (2) the ease of remittance financial infrastructure. This study uses qualitative data collection methods to reveal the empirical reality experienced by domestic workers from Indonesia in Hong Kong. As a result, there is a relevance of the financial infrastructure factor for remittances to the experience in Hong Kong during the Covid-19 pandemic. This study found several other factors that were not proposed by Ratha, namely the struggle of migrant workers unions in Hong Kong to respond to the crisis period and the existence of politics of surviving. This politics of surviving is similar to the concept of ‘double movement’ from Karl Polanyi (2001). This factor together with two other factors is cause of the stability of remittances to Indonesia. Comparison with other countries will also show other factors that cause remittances remain stable during the Covid-19 pandemic.